PEMBERDAYAAN PENYANDANG TUNAGRAHITA MELALUI PELATIHAN KETERAMPILAN DARI KORAN BEKAS - Bastiana; Hadi, Purwaka; Meidina, Tatiana; Kasmawati, St.; Rasyid, Rusman (Transpublika Publisher, 2022)
After completing their education at Special Education School (SLB), intellectually disabled students have to return to their community. Therefore, it is necessary to provide them with simple skills of making use of used newspapers. This study was intended to provide the teenage intellectually disabled students of SLB YP3LB Makassar with the skill that would enable them to live independently. The training was given to 5 mentally disabled students of vocational class at SLB YP3LB Makassar. The methods used were socialization, training, and practice. The findings indicate that the empowerment in form of training to make handicrafts from used newspaper is good for intellectually disabled students. The training was successful because (1) the skills trained were been mastered by the participants, (2) the materials and tools used were well known to participants, (3) the activities were organized in simple ways, (4) the examples and instructions were clearly stated, (5) and time allotted was enough for participants to do the steps correctly. It is suggested that the ability of students with intellectual disabilities in making use of newspapers can be improved in various forms. The skills will be able to help intellectually disabled students to live independently using the skills to make a living.